Analisis Kesiapan Pengguna Simrs dan Rekam Medis Elektronik (RME) dengan Metode Tri 2.0 di RSGM Universitas Jember - Assofan, Walid Attorik A Jabar; Hardiana, Hedy (Jurnal Ners, 2024)
Healthcare 4.0 presents a promising new vision for the healthcare industry, including hospitals. Its objective is to offer superior, value added health services, while simultaneously enhancing the effectiveness and efficiency of the healthcare industry. Consequently, it will effectively boost the quality, significance, productivity, cost-effectiveness, and efficiency of healthcare services and elevate patient satisfaction. Electronic Medical Records (EMR) and SIMRS are two technologies undergoing implementation and advancement. However, numerous hospitals have yet to realize optimal implementation. The Technology Readiness Index (TRI) serves as a user readiness parameter for adopting and utilizing new technology. The questionnaire comprised 44 items to assess users' readiness. The validity test demonstrated that all items were valid (r count > r table) and the questionnaire Cronbach's Alpha respectively indicating reliability. The questionnaire design can be used to evaluate the preparedness of SIMRS and electronic medical record (RME) users in hospitals using the technology readiness index approach. Further research is necessary to implement the questionnaire design.